MEMBANGUN GENERASI BERKARAKTER ISLAMI MELALUI PENDIDIKAN AGAMA DAN MORAL DI TK PERMATA BUNDA - Fauziah, Nurul; Fitriyah Nur Azizah; Nur Istiana Makarau; Restu Hoeruman, Moh; Mustapa Ahmad (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2024)
Various reviews and examinations of previous researchers on children's character building have been conducted. This is based on the realisation that character building is one of the main goals of education, especially in early childhood education (PAUD) which is known as the golden period of child development. Therefore, this study aims to analyse the implementation of religious and moral education at Permata Bunda Kindergarten in shaping children's character. Using a descriptive qualitative approach, this research involved teachers, students, and parents as the main subjects. The results show that religious education is integrated through habituation, storytelling method, and practical learning, such as ablution and prayer. In addition, the use of learning media in character building is also proven to be an important role in the process of building a generation with character. So that the utilisation of media is highly recommended as one of the strengthening of Islamic character in children. Through this research, it is concluded that in addition to exemplary aspects and habituation methods, providing learning experiences with the use of media is an important factor in building a generation of Islamic character from an early age. This is because children who grow up with the values of honesty, compassion, and responsibility will be better prepared to face the challenges of life in the future.